Association Between Migration, Education, and Re-employment During the Covid-19 Pandemic in Kalimantan Selatan Province - Maulana, Arif (Jurnal Kebijakan Pembangunan, 2025)
The Covid-19 pandemic has spread in Indonesia and caused an increase in unemployment, including in the Kalimantan Selatan Province. This research aims to analyze the relationship between migration, education, and the re-employment status of workers affected by layoffs in the early part of the Covid-19 pandemic using Sakernas August 2021 data. The analysis used was a multinomial logit model. The findings are that the labor force's migration and education status significantly impacted re-employment. High-education natives are more likely to be re-employed in formal employment than high-education migrants. On the other hand, low-education natives are more likely to be unemployed or less likely to be re-employed in formal employment than high-education migrants. In addition, low-education natives are more likely to be re-employed in informal employment than high-education migrants. These findings show that education is essential in increasing the chances of the native labor force getting better labor market outcomes.